2018
DOI: 10.2147/opth.s160961
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal aflibercept for exudative age-related macular degeneration with good visual acuity: 2-year results of a prospective study

Abstract: PurposeWe report the 2-year outcomes of intravitreal aflibercept (IVA) for exudative age-related macular degeneration (AMD) with good visual acuity (VA) and examine the baseline factors associated with good visual outcome.Materials and methodsThis multicenter, prospective study evaluated 39 eyes (39 AMD patients) enrolled from August 2013 to August 2014 at 12 and 24 months. Only patients with initial best-corrected VA (BCVA) >0.3 logarithm of the minimum angle of resolution (20/40 Snellen) were eligible. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…As for follow-up intervals, both of those previous studies had follow-up examinations monthly, while in the current study, follow-up visits were scheduled only every 1 to 3 months. Therefore, recurrence could have [41]. The mean change of log-MAR BCVA they reported was similar to our study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…As for follow-up intervals, both of those previous studies had follow-up examinations monthly, while in the current study, follow-up visits were scheduled only every 1 to 3 months. Therefore, recurrence could have [41]. The mean change of log-MAR BCVA they reported was similar to our study.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, recurrence could have been detected late, which would have resulted in delayed administration. However, similar to current study, Sakamoto et al, who injected intravitreal aflibercept in PCV with good visual acuity, showed no significant improvement in BCVA at 12 months [ 41 ]. The mean change of logMAR BCVA they reported was similar to our study.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Regardless of study type, intravitreal aflibercept administered in a bimonthly regimen following three initial monthly doses was consistently associated with gains in VA at Year 1, with improvements in vision ranging from +3.0 to +8.0 letters from baseline. [48][49][50][51][52][53][54][55][56] Talks et al concluded that the VA gains observed were comparable to those reported in the VIEW 1 and 2 phase III trials. 48 Several real-world studies have compared the effectiveness of intravitreal aflibercept bimonthly treatment with intravitreal aflibercept and ranibizumab PRN regimens.…”
Section: Fixed Bimonthly Dosingmentioning
confidence: 55%